Digital competence and performance of ASN in Educational Institutions: Analysis of interpersonal communication mediation in Siak Sri Indera Pura Regency - Maizon, Hepi; Ahman, Eeng; Yuniarsih, Tjutju; Santoso, Budi (ARKA INSTITUTE, 2025)
This study investigates the influence of digital competence on the performance of Aparatur Sipil Negara or ASN or civil servants within educational institutions in Siak Regency, Indonesia. Amidst growing demands for digital transformation in public service, technical skills alone are often insufficient without the support of relational competencies such as communication. Grounded in the Technology Acceptance Model (TAM), this research examines how interpersonal communication mediates the relationship between digital competence and ASN performance. A quantitative explanatory approach was employed, involving 50 ASN respondents selected through purposive sampling. Data were collected using structured questionnaires adapted from validated instruments, and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS 4.0. The results indicate that digital competence has a significant direct effect on ASN performance, while also indirectly enhancing performance through improved interpersonal communication. The mediating role of communication was confirmed as statistically significant, suggesting that digital competence promotes relational fluency, which in turn facilitates better task execution and coordination. These findings offer both theoretical and practical insights, particularly in the context of local public institutions in developing regions. Theoretically, the study expands the TAM framework by incorporating human interaction factors. Practically, it recommends that digital training for ASN should include not only technical modules but also communication skills development. This study concludes that sustainable digital transformation in the public sector requires simultaneous investment in both technology and people—particularly in building communicative capacity as the foundation of effective governance.